2022
DOI: 10.1111/tpj.15970
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms governing codon usage bias and the implications for protein expression in the chloroplast of Chlamydomonas reinhardtii

Abstract: Chloroplasts possess a considerably reduced genome that is decoded via an almost minimal set of tRNAs. These features make an excellent platform for gaining insights into fundamental mechanisms that govern protein expression. Here, we present a comprehensive and revised perspective of the mechanisms that drive codon selection in the chloroplast of Chlamydomonas reinhardtii and the functional consequences for protein expression. In order to extract this information, we applied several codon usage descriptors to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 209 publications
0
4
0
Order By: Relevance
“…The biological process of genetic information from mRNA to protein depends on codon coding [ 34 ]. Codon is an important part of the output of nucleic acid information [ 35 , 36 ]. Previous research has found that codon usage bias is mainly influenced by mutation pressure and natural selection [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biological process of genetic information from mRNA to protein depends on codon coding [ 34 ]. Codon is an important part of the output of nucleic acid information [ 35 , 36 ]. Previous research has found that codon usage bias is mainly influenced by mutation pressure and natural selection [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Codon bias can have a significant impact on a variety of cellular processes and characteristics, such as transcription, translation efficiency and accuracy, mRNA stability, and protein expression, structure, function, and folding during cotranslation ( Chaney and Clark, 2015 ; Fages-Lartaud et al, 2022 ). Codon bias has an influence on transcription due to its effect on chromatin structure and mRNA folding, which in turn affects translation efficiency by influencing the rate of translation elongation ( Hia et al, 2019 ; Hia and Takeuchi, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…After long-term development and evolution, organisms develop a certain preference for codons. The primary goals of codon usage preferences are to optimize translation yield and accuracy, protect protein structure and function, and manage resources to optimize cellular adaptation [10]. Studying codon usage patterns is an excellent way to understand biological evolution and phylogeny, as well as predict the expression and functional dynamics of unknown genes more accurately [11].…”
Section: Introductionmentioning
confidence: 99%